2021
DOI: 10.1016/j.ajog.2021.04.261
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for severe preeclampsia, hemolysis, elevated liver enzymes, and low platelet count syndrome, and eclampsia at preterm and term gestation: a population-based study

Abstract: BACKGROUND:The majority of previous studies on severe preeclampsia, eclampsia, and hemolysis, elevated liver enzymes, and low platelet count syndrome were hospital-based or included a relatively small number of women. Large, population-based studies examining gestational ageespecific incidence patterns and risk factors for these severe pregnancy complications are lacking. OBJECTIVE: This study aimed to assess the gestational ageespecific incidence rates and risk factors for severe preeclampsia, hemolysis, elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
4
35
0
1
Order By: Relevance
“…Our study found that pregnant women with HELLP syndrome were approximately 4-fold increased odds of preterm birth. This finding is consistent with findings from previous retrospective cross-sectional study by Lisonkova et al ( 27 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study found that pregnant women with HELLP syndrome were approximately 4-fold increased odds of preterm birth. This finding is consistent with findings from previous retrospective cross-sectional study by Lisonkova et al ( 27 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the risk of preterm birth associated with HELLP syndrome may be due to its association with preeclampsia ( 26 ). Although HELLP syndrome is sometimes considered to be a form of severe preeclampsia, the major distinct features include abnormal liver function, moderate-to-severe thrombocytopenia accompanied by microangiopathic haemolytic anemia, disrupted or destroyed erythrocytes on peripheral smear, and symptoms such as epigastric pain, nausea, and vomiting ( 27 ). Our study found that pregnant women with HELLP syndrome were approximately 4-fold increased odds of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…HELLP syndrome risk factors mirror those of preeclampsia with older (>35 years) mothers at highest risk. 101,102…”
Section: Epidemiologymentioning
confidence: 99%
“…The HELLP syndrome is a rare (0.5-0.9%) but serious complication of pregnancy or puerperium, associated with a higher risk of maternal and fetal mortality and morbidity [1][2][3][4][5][6]. Liver and spleen hematomas rarely entangle (<2%) HELLP cases [7,8], but rupture of the hematomas is a state of immediate threat to life [5,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed diagnosis of the HELLP syndrome may increase potential maternal and fetal mortality and morbidity. However, early diagnostic of HELLP can be a challenge: (1) This syndrome most often occurs in conjunction with preeclampsia (PE), a severe form of pregnancy-induced hypertension (PIH), but can occur on its own (in 10-30% of cases) [3,18,19]. Risk factors for HELLP are similar to those for other PIH forms [19][20][21][22]; (2) Prodromal symptoms of HELLP are nonspecific (malaise, nausea, epigastric pain, headache or visual symptoms) [3,23] but these prodromal symptoms may not be present either [2,3]; (3) Importantly, HELLP syndrome belongs to a broad spectrum of thrombotic microangiopathies (TMAs) characterized by hemolytic anemia, thrombocytopenia and organ damage as a result of microclots.…”
Section: Introductionmentioning
confidence: 99%